Buy Now, Pay Later And Generation Z Financial Well-Being: A Systematic Literature Review - Dhea Aulia Islami; Yudi Nur Supriadi; Ranila Suciati (UNIVERSITAS PAKUAN, 2026)
This study synthesizes evidence on how Buy Now, Pay Later (BNPL) affects financial stress and financial well-being among Generation Z. A systematic literature review was conducted using publications retrieved from Scopus through Publish or Perish, Google Scholar, and SINTA. The search covered studies published from 2018 to 2025. After title, abstract, keyword, and full-text screening against predefined inclusion and exclusion criteria, 30 relevant studies were analyzed through thematic synthesis. The literature consistently shows that BNPL expands short-term purchasing access and increases transaction value by reducing the perceived immediacy of payment. However, installment framing, promotional intensity, and frictionless checkout can encourage impulsive buying, overspending, multiple repayment obligations, and over-indebtedness. The effect on financial well-being is therefore conditional rather than uniformly negative or positive. Responsible financial behavior and self-control emerge as central mechanisms, while financial literacy is most effective when it is translated into budgeting, repayment discipline, and deliberate credit use. The review proposes a conditional framework in which BNPL usage influences financial stress and well-being through behavioral and psychological pathways. The findings support stronger consumer protection, transparent product design, risk-sensitive credit limits, and targeted financial education for young users.